Development of a Non-Motor Fluctuation Assessment Instrument for Parkinson Disease - Galit Kleiner-Fisman; Rebecca Martine; Anthony E. Lang; Matthew B. Stern (Parkinson's Disease)
Patients with Parkinson disease are increasingly recognized to suffer from non-motor symptoms in addition to motor symptoms. Many non-motor symptoms fluctuate in parallel with motor symptoms and in relationship to plasma levodopa levels. Though these symptoms are troublesome and result in reduced quality of life to patients and their caregivers, there has not been an objective method of recognizing and quantifying non-motor fluctuations (NMFs). This study sought to develop a patient-based instrument that would accurately capture the experience of patients with NMFs. Patient-based nominal group technique sessions, focus groups, and expert opinion were utilized in developing this questionnaire.